U-Multirank and Latin American Universities - García De Fanelli, Ana (International Higher Education, 2016)
The first U-Multirank launched in 2014, a multi-dimensional and user-driven approach to international ranking in higher education, included only a few Latin American universities. I address whether more Latin American universities will be able to participate in this interesting initiative in the near future. I first describe similar projects in Latin America and then discuss whether some of the data the U-Multirank requests in the institutional questionnaires can feasibly be collected from LA universities.